Impact of dairy manure addition on soil nutrients in northeast and south central Kansas - Strahm, T.; Harner, Joseph P.; Murphy, James P.; McCormack, G.; Smith, John F., 1962-; Key, David V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty four percent of the fields (14 of 22) in northeast and south central Kansas would be able to apply dairy manure on a nitrogen basis if the current swine manure application regulations were adopted. Due to high phosphorus levels in some fields, two of the 11 fields in northeast Kansas could not have any manure applied to them. Two other fields in northeast and four fields in south central Kansas would have to limit manure application rates to annual phosphorus required by the crops. Our results indicate minimal accumulation of nitrogen and potassium in the soil profile.
Keywords: Dairy; Nutrients; Soil; Manure